2017
DOI: 10.1097/pec.0000000000000464
|View full text |Cite
|
Sign up to set email alerts
|

What do Clinicians Perceive as a Successful “Trial of Fluids”?

Abstract: In children undergoing trial of fluids, we found that most clinicians perceived a fluid intake greater than 9 mL/kg as adequate and lower than 5 mL/kg as inadequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…1 Previous studies found that fluid intake greater than 9 mL/kg was adequate and less than 5 mL/kg was inadequate. 4 Although not superior to one another, children in both the INF and OA groups consumed a significantly larger amount of fluid in 1 hour. In addition, although not statistically different, both groups experienced a considerable reduction in pain.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…1 Previous studies found that fluid intake greater than 9 mL/kg was adequate and less than 5 mL/kg was inadequate. 4 Although not superior to one another, children in both the INF and OA groups consumed a significantly larger amount of fluid in 1 hour. In addition, although not statistically different, both groups experienced a considerable reduction in pain.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies found that fluid intake greater than 9 mL/kg was adequate and less than 5 mL/kg was inadequate. 4 In addition, a review of expert opinion concluded that a difference of 4 mL/kg during oral rehydration therapy is clinically important. 1 Power analysis showed that 34 patients were required to achieve an 81% power to detect a difference of 4 mL/kg with an α value of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations